EBV mononucleosis in children in modern conditions - J. K. Hakizimana; V. N. Timchenko; M. A. Shakmaeva; T. A. Kaplina; M. D. Subbotina; S. L. Bannova; A. V. Fedorova; V. F. Sukhovetskaya; E. B. Pavlova; N. V. Pavlova (Детские инфекции (Москва))
EBV-mononucleosis is a widespread infectious disease, and also it is an urgent problem of the whole world. The purpose of the research was to study the clinical and laboratory features of EBV-mononucleosis in hospitalized children of different ages in modern conditions. Under the supervision were 136 children aged from 1 year to 18 years. All of the patients had typical and mainly (85%) moderate form of the disease, and 15% of them patients had a severe form of the disease. The results: more severe fever and lymphadenopathy were observed in children older than 3 years. Acute tonsillitis was present in all hospitalized children. Adenoiditis and hepatosplenomegaly were greater in the group of patients of a younger age. Hyperfermentemia was determined in more than half of patients, more often in children over 12 years old. In the hemogram leukocytosis and monocytosis were mostly noted. Atypical blood mononuclear cells were detected in 89% of patients. Patients got complex etiopathogenetic therapy.